Petrography and geochronology of the Furquim Quartzite, an eastern extension of the Itacolomi Group (Quadrilátero Ferrífero, Minas Gerais) - Jordt-Evangelista,Hanna (2015)
Abstract This paper presents the results of a petrographic and geochronological investigation of the Furquim Quartzite (FQ) to establish its stratigraphic correlation to quartzitic units of the Quadrilátero Ferrífero (QF) province. The Quartzite comprises a ca. 20km long and 1-6km wide ridge overlying discordantly the Archean to Paleoproterozoic gneissic basement and rocks of the Archean Rio das Velhas Supergroup between the city Mariana and the town Furquim, southeast of the QF. Despite the discordant contacts, previous field-based stratigraphic studies considered the Furquim Quartzite as part of the Archean Maquiné Group – top unit of the Rio das Velhas Supergroup. U-Pb zircon geochronology via LA-ICP-MS identified several detrital populations ranging from Paleoproterozoic to Archean age. The youngest population of 2087±19 Ma defines the maximum age for the sedimentation of the precursor sandstone. This age can be correlated to be the age of the youngest zircon population of the Itacolomi Group quartzites in the QF. Thus, in contrast to previous studies, the results indicate that the FQ is an eastern extension of the Itacolomi Group, the youngest unit of the Paleoproterozoic Minas Supergroup.